Investigating the Bounds of Quality Factor for Class-E Series-Tuned RF Power Amplifiers and Their Computer-Aided Optimization - Pallab Kr Gogoi; Ayan Sharma; Jurgen Vanhamel; Jérôme Loicq (Applied Sciences)
This paper presents a comprehensive analysis of Class-E series-tuned radio-frequency power amplifiers (RFPAs), focusing on their design and optimization for high efficiency and performance. However, achieving optimal performance involves navigating trade-offs among efficiency, bandwidth, harmonic suppression, output power capability, and device stress. This work examines the trade-offs involved in the series-tuned (<semantics>Ls−Cs</semantics>) network and establishes the bounds for its quality factor using computer-aided harmonic balance (HB) simulations. Additionally, it explores optimal harmonic termination strategies to enhance the performance and efficiency of the design. Finally, a novel methodology using harmonic termination is proposed, simplifying the design process by eliminating the need for traditional load-pull extraction methods.